My parents$1 (Bdivorce s - Cole, Julia (Brookfield, Conn. : Copper Beech Books, 1998)
Discusses why divorce happens, how to cope with it, and how to deal with difficult feelings as well as friends whose parents are divorced.
Includes index.
Keywords: Children of divorced parents -- Psychology -- Juvenile literature; Divorce -- Juvenile literature; Divorce